Study on the visual aspects of urban design in the vicinity of the Shwedagon Pagoda - Nandar, Linn (2008)
Yangon, the capital of Myanmar, is developing along with the changing aspects of socio-economic developments. The earliest accounts of Yangon are always associated with the Shwedagon Pagoda. The Shwedagon is the cultural lighthouse as well as a landmark of Myanmar. The ancient Myanmar planned this pagoda to attain visual supremacy and dominance over its environs. Conservation of such a historical heritage is to be regarded as our national concern. Some newly built buildings have become visual obstructions to the Shwedagon in the recent years. This situation calls for a scientific study and decisive actions in urban planning of Yangon. It is in need of strict regulations to preserve and protect visual axes of the Shwedagon. There has been a restriction for over six-storeyed buildings in the preservation area of the Shwedagon according to the 1996 Yangon municipal bylaw. However, these are not supposed to meet the actual requirements of present situation. Proper recommendations for newly built buildings in the environs of the Shwedagon need to be considered from visual aspects of urban design.The first portion of this paper is to review and study the traditional practices of urban planning in comparison with present conditions in the immediate vicinity of the Shwedagon. The critical analysis is made from visual aspects of urban design. Secondly, individual axes of the Shwedagon are found out and identified based on the present and past conditions. The last portion of this paper is providing specific guidelines to protect these visual axes of the Shwedagon with its setting. This may be a contribution to current and future efforts to conserve a landmark in the planning and development of a modern city.